Financial Performance, Struktur Modal dan Arus Kas Operasi Terhadap Return Saham Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia - Nadila Andriliyani; Anisa Anisa (Jurnal Ilmu Manajemen METHONOMIX, 2024)
This study aims to determine the effect of financial performance, capital structure, and operating cash flow on stock returns. Financial performance in this study is proxied by Return On Assets and Return On Equity and capital structure is measured by Debt to Equity ratio. This type of research is quantitative research with secondary data sources. The population in this study amounted to 124 companies in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange in 2018-2022. The sample selection method used in this study is the purposive sampling method so that the samples obtained by this method are 25 companies. The data analysis technique used is panel data regression analysis using Eviews 12 software. The results showed that simultaneously financial performance proxied with return on assets, financial performance proxied with return on equity, capital structure, and operating cash flow together affect stock returns. However, partially the financial performance variables proxied by return on assets and capital structure affect stock returns. Meanwhile, financial performance proxied by return on equity and operating cash flow has no effect on stock returns.